Analysis of The Effect of Pollinating Insects (Elaeidobius Kamerunicus) on Oil Palm Average Bunch Weight in Sei Silau Plantation of PT Perkebunan Nusantara IV Regional I - Farid Nurhidayah; Bahrul Ulum; Alfiq Muhammad Pane; Audialiy Dewfan; Nur Jannah Nasution (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Oil palm (Elaeis guineensis Jacq.) is an important plantation commodity whose productivity is closely related to the quality and yield of fresh fruit bunches (FFB). One of the main indicators of production performance is average bunch weight, which is strongly influenced by the success of pollination. This study aimed to evaluate the differences in average bunch weight before and after the introduction of the pollinating insect Elaeidobius kamerunicus. A quantitative comparative method with paired observations on the same plantation blocks was applied in this study. The data were obtained from production records in Afdeling II of Sei Silau Plantation, covering the periods of July–August 2025 (before insect introduction) and January–February 2026 (after introduction). Data analysis was conducted using the Shapiro–Wilk normality test, followed by the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed that the average bunch weight after the release of pollinating insects was consistently higher than before the introduction. Statistical analysis also revealed significant differences, with p-values of 0.001 and 0.008 (p 0.05). These findings indicate that the presence of Elaeidobius kamerunicus improves pollination efficiency, thereby enhancing fruit formation and bunch weight. This study highlights the importance of effective pollinator management as a strategy to improve oil palm productivity in plantation systems.